Social science perspectives on managing agricultural technology - Groenfeldt, D.; Moock, J.L. (International Irrigation Management Institute, 1989)
Experiences of 15 social science research fellows who recount their roles in particular research projects at the International Agricultural Research Centers they were appointed . In addition to highlighting the contributions social scientists can make in the field of agricultural research, their papers offer a candid look at the kinds of work in which the Centers currently are engaged.